Influence of fermented horse milk supplementation on immunity against hepatitis A vaccine in Balb/c mice - Sasmito, Ediati; ., Rumiyati; W., Sri Rahayu; Andriyani, Evie; Istikharah, Rochmy (INDONESIAN JOURNAL OF PHARMACY, 2006)
It has been evaluated the influence of fermented horse milk into Balb/c mice on immunity against hepatitis A vaccine. The study employed a complete randomized design using thirty mice which were divided into 3 groups. Each group orally consumed fermented horse milk at dose 0.4 mL/20g body weight, levamisole (as positive control) at dose 0.4 mL/0.45 mg/20g body weight and distilled water (as negative control) at dose 0.4 mL/20g body weight respectively on a daily basis in addition to the standard diet for 46 days. The mice were immunized intraperitoneally (3 times) at d 7, d 28, and d 42, with 0.65 Î¼g/20g body weight of hepatitis A vaccine. Blood samples were collected from plexus retroorbitalis using heparinized capillary one week after first (d 14), second (d 35) and 4 days (d 46) after third immunizations, and then mice were sacrificed to isolate the lymphocytes. The IgM, IgG and IgA titers in the sera and the culture media were measured by ELISA.The IgM (except d 46), IgG (subtype IgG1 (except d 14), IgG2a, IgG2b, IgG3 (except d 35), and IgA titers in the sera significantly higher (p<0.05) than controls. This difference was associated with enhanced in vitro antibodies secretion by cultured lymphocytes isolated from the spleen for IgA. The result suggested that orally fermented horse milk supplementation inhances immunity against hepatitis A vaccine in Balb/c mice. The SDS-PAGE showed that 30-kDa proteins were present in fermented horse milk as well as fermented cow milk, but 7.4-kDa protein present only in fermented horse milk.Key words : fermented horse milk, immunity, hepatitis A vaccine, Balb/c mice.